2017
DOI: 10.1016/j.cobeha.2017.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Immune signaling mechanisms of PTSD risk and symptom development: insights from animal models

Abstract: Post-traumatic stress disorder (PTSD) is characterized by persistent re-experiencing of a traumatic event, avoidance, and increased arousal. The approved pharmacological treatments for PTSD have limited efficacy (~60% treatment response), supporting the need for identification of biomarkers and novel pharmacological therapies. Mounting evidence suggests increased inflammatory markers and altered immune gene expression correlate with the severity of symptoms in PTSD patients. However a causal role of immune sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 68 publications
0
23
0
7
Order By: Relevance
“…Inflammatory responses in animal models were seen in specific brain regions and throughout the system. A predator-exposure rat study found increased proinflammatory cytokines in the hippocampus, amygdala, and prefrontal cortex, with a concomitant reduction in anti-inflammatory cytokines (58,59). Similarly, a stress-enhanced fear-learning model showed increased hippocampal IL-1b concentrations, and the learning decrement was prevented by blocking central IL-1b signaling after the stress (60).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…Inflammatory responses in animal models were seen in specific brain regions and throughout the system. A predator-exposure rat study found increased proinflammatory cytokines in the hippocampus, amygdala, and prefrontal cortex, with a concomitant reduction in anti-inflammatory cytokines (58,59). Similarly, a stress-enhanced fear-learning model showed increased hippocampal IL-1b concentrations, and the learning decrement was prevented by blocking central IL-1b signaling after the stress (60).…”
Section: Preclinical Studiesmentioning
confidence: 99%
“…There is already considerable evidence for a significant association between inflammation and PTSD diagnosis (Breen et al, 2018;Brudluy et al, 2015;Michopoulos et al, 2015;Miller et al, 2018;Spitzer et al, 2010). Moreover, there is prospective evidence that inflammation may be a risk factor for PTSD emergence (Breen et al, 2015;Eraly et al, 2014) and that it affects fear circuits and processes (Deslauriers, Powell, & Risbrough, 2017). Taken together with findings of the present study, it is thus conceivable that pre-deployment sleep disturbance among military personnel may have resulted in an increase in inflammatory signalling which predisposed to the development of re-experiencing symptoms following trauma exposure (Besedovsky, Lange, & Haack, 2019).…”
Section: ;mentioning
confidence: 99%
“…Other established biological phenotypes include increased activity/function of amygdala, reduced function and structural abnormalities in prefrontal cortex (PFC) and hippocampus (69). PTSD is consistently associated with increased inflammation both as a risk factor and in relation to symptom state (10). Finally, sleep disturbances, including reduced sleep duration or fragmented rapid eye movement (REM), are commonly described in PTSD (6).…”
Section: Introductionmentioning
confidence: 99%